Efficient algorithm to compute the Berry conductivity - Markus Muller (New Journal of Physics, 2014)
We propose and construct a numerical algorithm to calculate the Berry conductivityin topological band insulators. The method is applicable to cold atomsystems as well as solid state setups, both for the insulating case where the Fermienergy lies in the gap between two bulk bands as well as in the metallic regime.This method interpolates smoothly between both regimes. The algorithm isgauge-invariant by construction, efficient, and yields the Berry conductivity withknown and controllable statistical error bars. We apply the algorithm to severalparadigmatic models in the field of topological insulators, including Haldaneʼsmodel on the honeycomb lattice, the multi-band Hofstadter model, and the BHZmodel, which describes the 2D spin Hall effect observed in CdTe/HgTe/CdTequantum well heterostructures.